A novel miniaturized metamaterial lens antenna. Issue 7 (6th March 2020) - Luo, Man; Sang, Xiangyuan; Tan, Jing; Chen, Juan
Abstract: This article develops a flat, miniaturized lens based on metamaterial for antenna gain improvement. The overall size of the lens is 1.9 λ 0  × 1.9 λ 0  × 0.05 λ 0 . The distance between the metamaterial lens and the antenna is only about 0.4λ0 . The prototype lens antenna is fabricated and the measured results are in agreement with the simulated results. It shows that the proposed lens provides significant gain enhancement by 2 to 3.5 dB between 1.3 and 1.45 GHz, which effectively demonstrate a high directivity, miniaturized, and compact metamaterial lens antenna.